Patterns Of Malnutrition In Children With Cyanotic And Acyanotic Congenital Heart Disease. - Amonkar, Priyanka; Lalwani, Nikita; Gavhane, Jeetendra; Kadam, Nitin (Journal of Neonatal Surgery, 2026)
Background: Congenital heart disease (CHD) is a common congenital anomaly in children and is frequently associated with growth failure and malnutrition due to increased metabolic demands, feeding difficulties, recurrent infections, and chronic hypoxia. Objectives: To assess the nutritional status of children with congenital heart disease and to compare patterns of malnutrition between cyanotic and acyanotic heart lesions. Methods: This observational, analytical, cross-sectional study was conducted at a tertiary care hospital over a period of three years. Sixty-five children aged between one month and 18 years with echocardiographically confirmed congenital heart disease were enrolled. Anthropometric measurements including weight, height/length, and mid-upper arm circumference were obtained using standardized methods. Nutritional status was evaluated using weight-for-age, height-for-age, and weight-for-height indices based on WHO growth standards, along with IAP and Wellcome Trust classifications where appropriate. Statistical analysis was performed to compare nutritional parameters between cyanotic and acyanotic CHD groups. Results: Among the 65 children with congenital heart disease studied, malnutrition was highly prevalent with over four-fifths of the study population exhibiting some degree of undernutrition. Children with cyanotic CHD demonstrated significantly higher rates of underweight, stunting, and wasting compared to those with acyanotic CHD. Severity of wasting was also associated with increasing age. Conclusion: Malnutrition remains a major comorbidity in children with congenital heart disease, particularly among those with cyanotic lesions. Routine nutritional assessment and early, targeted nutritional intervention should be integrated into the comprehensive management of children with CHD to improve growth outcomes and overall prognosis.. ..